Pengaruh Penyesuaian Nilai Jual Objek Pajak (NJOP) Terhadap Kemauan Membayar Pajak Bumi dan Bangunan di Kota Palembang - Weny Putri; Feby Astrid Kesaulya; Khairunnisa Khairunnisa (Kompartemen : Jurnal Ilmiah Akuntansi, 2020)
This study aims to determine the effect of adjusting the Sales Value of Taxable Objects which is the basis for the imposition of Property Tax (PBB) in Palembang on the willingness of taxpayers to pay PBB. The analysis used is Regression. The results showed that there was an effect of the NJOP adjustments to the taxpayer's willingness to pay taxes. The people feel that they are not too charged with the tariff increase and are still willing to pay the tax. Moreover, tax is protected by law that make taxpayers have to continue paying taxes in accordance with the tax debt stated in the Property Tax Assessment Letter